2022
DOI: 10.3390/ijerph191811180
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Symptoms, Allergies, and Environmental Exposures in Children with and without Asthma

Abstract: Background: Epidemiological data concerning the level of asthma morbidity indicate that in Poland, asthma is diagnosed in 5–10% of the pediatric population. Aim The purpose of this study was to compare the prevalence of respiratory symptoms and allergies in a group of children with and without asthma and to evaluate the association between exposure to environmental factors and the prevalence of bronchial asthma in a pediatric population. Material and Methods: A cross-sectional study was conducted on a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The diagnosis of BA was considered using the medical history, family history, clinical examination, and symptoms including episodic dyspnea, coughing, wheezing, and tightness in the chest, as well as laboratory findings. The results of pulmonary function tests allowed for the confirmation of the diagnosis of BA and a determination of the severity and reversibility of airflow restriction[ 7 , 8 ]. Malnutrition was defined using World Health Organization definitions[ 9 - 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…The diagnosis of BA was considered using the medical history, family history, clinical examination, and symptoms including episodic dyspnea, coughing, wheezing, and tightness in the chest, as well as laboratory findings. The results of pulmonary function tests allowed for the confirmation of the diagnosis of BA and a determination of the severity and reversibility of airflow restriction[ 7 , 8 ]. Malnutrition was defined using World Health Organization definitions[ 9 - 12 ].…”
Section: Methodsmentioning
confidence: 99%
“… 89 Particularly when combined with viral illnesses and high levels of air pollution, persistent exposure to the suspected allergens can cause poorly managed asthma. 90 Moreover, it has been demonstrated that the chance of an exacerbation is correlated with allergen dose. 91 Therefore, for children with DA, it is important to systematically assess allergen exposure.…”
Section: Evaluation and Management Of Damentioning
confidence: 99%
“…They are related to environmental factors and are most often analyzed together. It is estimated that asthma may affect about 10% of children in Poland, but its prevalence may vary depending on environmental or social factors [ 8 ]. The cohort study ECAP (Epidemiology of allergic diseases in Poland) confirms the incidence of this disease in the pediatric population aged 6–7 years at the level of 4.4% among children living in urban areas and 3.9% living in rural areas [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no studies have been conducted in Poland to date on the social inequalities in asthma. Most studies have focused on the socioeconomic and environmental determinants of this disease [ 8 , 13 , 14 ]. However, simple analyses of the socioeconomic and environmental determinants of bronchial asthma do not fully explain the significance of social inequalities in this disease, but only indicate its social variation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation